Assessment of Natural Moisture Availability of Turkestan Region of the Republic of Kazakhstan - Gulnar Aldazhanova; Zhumakhan Mustafayev; Askhat Tuletayev; Irina Skorintseva; Amanzhol Kuderin (Faculty of Geography, Universitas Gadjah Mada, 2023)
To increase the level of management efficiency in the agricultural sector of the economy, it is necessary to ensure the implementation of the sustainable environmental management principles, taking into account the spatial patterns of climate change and bioclimatic potential of the territory. The assessment of natural moisture availability of the natural areas of the Turkestan region of the Republic of Kazakhstan for 1941-2020 (by providing a comparative analysis of indicators for 1941-1960 and 2001-2020) was conducted based on the use of the natural moisture coefficient and hydrothermal index or